2019
DOI: 10.1152/japplphysiol.00292.2019
|View full text |Cite
|
Sign up to set email alerts
|

“Beet” the cold: beetroot juice supplementation improves peripheral blood flow, endothelial function, and anti-inflammatory status in individuals with Raynaud’s phenomenon

Abstract: Raynaud’s phenomenon (RP) is characterized by recurrent transient peripheral vasospasm and lower nitric oxide (NO) bioavailability in the cold. We investigated the effect of nitrate-rich beetroot juice (BJ) supplementation on 1) NO-mediated vasodilation, 2) cutaneous vascular conductance (CVC) and skin temperature (Tsk) following local cooling, and 3) systemic anti-inflammatory status. Following baseline testing, 23 individuals with RP attended four times, in a double-blind, randomized crossover design, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 66 publications
1
27
0
1
Order By: Relevance
“…Beetroot juice consumption promotes an enhanced endurance performance in several populations of athletes [26], potentially due to improved vasodilatation, which facilitates an increase in blood flow to the exercised muscles [22,23] and stimulates a reduction in the O 2 needed during submaximal efforts [25]. However, in intermittent efforts, there is controversial evidence regarding the ergogenic effect of BJ [40,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beetroot juice consumption promotes an enhanced endurance performance in several populations of athletes [26], potentially due to improved vasodilatation, which facilitates an increase in blood flow to the exercised muscles [22,23] and stimulates a reduction in the O 2 needed during submaximal efforts [25]. However, in intermittent efforts, there is controversial evidence regarding the ergogenic effect of BJ [40,42].…”
Section: Discussionmentioning
confidence: 99%
“…After absorption in the oral cavity or the intestine, circulating NO 2 − serves as a substrate for O 2 − independent of NO generation, a process potentiated by hypoxia and acidosis conditions [20]. An increased NO presence derived from NO 3 − supplementation improves vasodilation, increasing blood flow to the muscles [21][22][23], and facilitates force production in vivo, reducing ATP cost in exercised muscles [24,25]. Hence, BJ supplementation has showed the capacity to improve endurance performance [26] and accelerate post-repeated-sprint recovery [27].…”
Section: Introductionmentioning
confidence: 99%
“…In some models, the pharmacological amelioration of endothelial dysfunction has been shown to prevent growth restriction (Sekimoto et al 2020). Supplementation with beetroot juice (either with or without nitrate) was shown to improve vascular reactivity of isolated uterine arteries in this mouse model and has also been shown to improve microvascular function in humans with Raynaud's disease (Shepherd et al 2019).…”
mentioning
confidence: 86%
“…Betalain pigments within nitrate-rich red beetroot have a variety of beneficial properties in inflammatory conditions including reducing oxidative stress [ 77 ]. In the rheumatic diseases, this has recently been demonstrated in Raynaud’s phenomenon (seen in appropriately a fifth of patients with RA), with marked reductions in pan-endothelin and blood pressure, as well as pro-inflammatory cytokines, on administration of beetroot juice [ 78 , 79 ]. A small cohort study of patients with RA also demonstrated significant improvements in endothelial function following two weeks of daily beetroot juice consumption [ 80 ].…”
Section: The Role Of Water and Fresh Fruit Juicesmentioning
confidence: 99%